Students' perceptions of endodontic typodont teeth with simulated canals printed from novel materials - Alexander Jon Cresswell-Boyes; Alexander Jon Cresswell-Boyes; Graham Roy Davis; Aylin Baysan (Frontiers Media S.A., 2024)
IntroductionThis study aimed to investigate students' perceptions of the use of 3D-printed typodonts by implementing a questionnaire and evaluating the students' comparisons between extracted, commercial and 3D-printed teeth.MethodsEthical approval was obtained (QMER20.586/2021) and questionnaire feedback was collected anonymously using an online survey. A total of 143 fourth- and fifth-year dental students were approached to participate during pre-clinical courses focussing on root canal therapy. The tooth design was based on micro-CT data of an extracted maxillary central incisor and 3D-printed with haptically-similar materials produced in previous work. The questionnaire comprised 11 Likert-scale questions, four open-ended questions, two "yes" or "no" questions and three closed-ended questions.ResultsEighty questionnaires were returned. Overall, the feedback was favourable towards the 3D-printed typodonts compared to the commercial teeth. The biggest difference in responses was in Question 6 related to the realism of drilling the enamel when comparing 3D-printed teeth with commercial ones. Statistical analysis showed a significant difference (p < 0.05); the fourth-year's response on average, was 2.95 (±0.73) an "agree" rating, whereas the fifth-year's response was 3.98 (±0.82) with "neither agree or disagree".DiscussionWithin the limitations of this study, the 3D-printed typodonts were rated high in comparison to the commercial teeth in terms of overall operative experiences.